Proceso de atención de enfermería (1999)
ABSTRACT: Nursing is the diagnosis and the treatment of human responses to actual or potential health problems. To do this, the nursing science is based on a wide theoretical framework. The nursing process is the method to apply this framework to the nursing practice. First, it ensures care quality for the patient’s attention. Second, it gives the basis for the operative control and the way to systematize and research in this area. In this review, the authors expose the concepts and steps of the nursing attention process.